The tumor suppressors p331NG1 and p331NG2 interact with alien in vivo and enhance alien-mediated gene silencing - Kob, Robert; et al. (Journal of Proteome Research, 2007)
The tumor suppressor p33ING1 is involved in DNA repair and cell cycle regulation. Furthermore, p33ING1 is a transcriptional silencer that recognizes the histone mark for trimethylated lysine 4 at histone H3. Interestingly, expression of p33ING1 and p33ING2 is able to induce premature senescence in primary human fibroblasts. The corepressor Alien is involved in gene silencing mediated by selected members of nuclear hormone receptors. In addition, Alien acts as a corepressor for E2F1, a member of the E2F cell cycle regulatory family. Furthermore, recent findings suggest that Alien is complexed with transcription factors participating in DNA repair and chromatin. Here, using a proteomic approach by surface-enhanced laser desorption ionization and mass spectrometry (SELDI-MS) combined with immunological techniques, we show that Alien interacts in vivo with the tumor suppressor p33ING1 as well as with the related tumor suppressor candidate p33ING2. The interaction of Alien with p33ING1 and p33ING2 was confirmed in vitro with GST-pull-down, suggesting a direct binding of Alien to these factors. The binding domain was mapped to a central region of Alien. Functionally, the expression of p33ING1 or p33ING2 enhances the Alien-mediated silencing, suggesting that the interaction plays a role in transcriptional regulation. Thus, the findings suggest that the identified interaction between Alien and the tumor suppressors p33ING1 and p33ING2 reveals a novel cellular protein network.
Keywords: corepressor; co-repressor; cellular senescence; transcriptinal silencing; tumor supressor